Correction: Alvarado et al. Alginate–Bentonite Encapsulation of Extremophillic Bacterial Consortia Enhances Chenopodium quinoa Tolerance to Metal Stress. Microorganisms 2024, 12, 2066 - Roxana Alvarado; Cesar Arriagada-Escamilla; Javier Ortiz; Reinaldo Campos-Vargas; Pablo Cornejo (Microorganisms)
In the original publication [...]